2021
DOI: 10.47836/pjssh.29.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of E-government: Does Citizens’ Access to ICT Matter?

Abstract: Different studies have evaluated the success of e-government in developed and developing countries. However, many of these studies rely on the economic and conventional approaches to evaluate e-government like other ICT projects. Also, they do not consider citizens’ access to ICT in their studies. This study, therefore, examines the moderating effect of citizens’ access to ICT on the performance of e-government within the context of IS Success Model and public value theory. The public value of e-government rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 93 publications
(120 reference statements)
0
8
0
1
Order By: Relevance
“…In other words, to understand the performance of e-agriculture, particularly from the users' perspective, it is vital to examine the adequate access to IT tools, user-friendly workoriented content, communities of practice, a culture of knowledge, capacity of learning, a spirit of cooperation, commercial and other incentives, and carefully measured capital investments and returns. Paying close attention to all the parameters of the 8Cs framework, it can be assisted to examine the success of IT practices in any sector [24,21,26,25]. Extensive review of the prior studies revealed that 8Cs framework is widely used to examine the readiness of egovernment, knowledge management practices and e-readiness in higher education.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, to understand the performance of e-agriculture, particularly from the users' perspective, it is vital to examine the adequate access to IT tools, user-friendly workoriented content, communities of practice, a culture of knowledge, capacity of learning, a spirit of cooperation, commercial and other incentives, and carefully measured capital investments and returns. Paying close attention to all the parameters of the 8Cs framework, it can be assisted to examine the success of IT practices in any sector [24,21,26,25]. Extensive review of the prior studies revealed that 8Cs framework is widely used to examine the readiness of egovernment, knowledge management practices and e-readiness in higher education.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In this line, Rao [23] considered the 8Cs: connectivity (affordability and widespread of ICT devices), content (useful of content and generate in local language), community (forum to discuss the issues), commerce (infrastructure for ecommerce), capacity (human resources such as technical, managerial, policy and legal to use ICTs), culture (forward-looking progressive influence to use ICTs), corporation (governmental support to use ICTs) and capital (adequate financial resources to use ICTs) as the checklist to measure the capacity of any country to be elaborate in e-readiness to make efficient businesses models or develop new export sectors. Rao's framework is furthered utilized to access the citizens' access to ICT on the performance of e-government [24,25] readiness of knowledge management practices by employees in IT companies such as JD Edwards, EDS, EMC, Novell, Open Text, Oracle, SAS, Sun Philippines and Xerox [26] and e-readiness in higher education context [21].…”
Section: Literaturementioning
confidence: 99%
“…[59] Innovation orientation [1], [11], [14], [45] Productivity [1], [11], [25] Satisfy users' needs [1], [11], [12], [17], [63], [68] Service enhancement [1], [4], [10]- [12], [14], [17], [19], [25], [37], [40], [50], [56], [69] Better management of public resources and funds [1], [11] Responsiveness [1], [4], [11], [12], [35], [50], [61], [67] Respect for the individual [1], [11], [63] 2. Improved Administrative Efficiency Accountability within public organization [1], [11], [17], [25], [51], [59] Cost reduction and savings [1], [11], [38] Competitiveness…”
Section: Public Value Dimensionmentioning
confidence: 99%
“…Reference public resource and funds Data integrity and quality [1], [11] Data immutability [1], [11] Predictive capabilities [1], [11] Reduced energy consumption Increased [1], [11] Increased resilience [1], [11] Economy and parsimony Open [1], [11], [12], [40] 3. Open Government (OG) capabilities Transparency and openness [1], [4], [9], [11], [14], [19], [35], [37], [40], [50], [67] Information quality [1], [4], [11], [12], [17], [19], [35], [50] System quality [1], [11], [12], [14], [17], [19] Service quality [1], [4], [10]- [12], [19], [25], [33], [35], [50],…”
Section: Public Value Dimension Public Value Criteriamentioning
confidence: 99%
See 1 more Smart Citation